Pain scores and recovery post tonsillectomy: intracapsular versus extracapsular coblation. Issue 9 (19th August 2019) - Junaid, M; Sood, S; Walijee, H; Dorgham, J; De, S
Abstract: Objective: This study compared post-tonsillectomy pain scores and recovery using the coblation-only technique, comparing extracapsular versus intracapsular approaches. Methods: A prospective study was performed in our paediatric ENT department. Pain scores were recorded on days 0, 2, 4 and 8, using a visual analogue scale ranging from 0 (no pain) to 10 (extreme pain). Information was also collected on: return to normal fluid and solid intake, and any post-operative visits to primary care. Results: In total, 101 patients were included in the analysis. Average pain scores were statistically lower on days 2, 4 and 8 in the intracapsular group compared to the extracapsular cohort. The intracapsular cohort also returned sooner to normal fluid and solids intake. The extracapsular group were more likely to visit the general practitioner post-operatively. Conclusion: Intracapsular tonsillectomy appears to result in reduced morbidity overall and should be considered as a viable alternative in relevant cases.